Food science and technology: challenges for Africa towards the year 2000 - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
Food science and technology: challenges for Africa towards the year 2000 edited by L T Marovatsanga and J N R Taylor 298pp ISBN 0 908307 47 0